On the Fatigue Performance of Friction-Stir Welded Aluminum Alloys - Sergey Malopheyev (Materials, 2020)
This work was undertaken in an attempt to ascertain the generic characteristics of fatigue behavior of friction-stir welded aluminum alloys. To this end, different alloy grades belonging to both the heat-treatable and non-heat-treatable types in both the cast and wrought conditions were studied. The analysis was based on the premise that the fatigue endurance of sound welds (in which internal flaws and surface quality are not the major issues) is governed by residual stress and microstructure. Considering the relatively low magnitude of the residual stresses but drastic grain refinement attributable to friction-stir welding, the fatigue performance at relatively low cyclic stress was deduced to be dictated by the microstructural factor. Accordingly, the fatigue crack typically nucleated in relatively coarse-grained base material zone; thus, the fatigue strength of the welded joints was comparable to that of the parent metal. At relatively high fatigue stress, the summary (i.e., the cyclic-plus residual-) stress may exceed the material yield strength; thus, the fatigue cracking should result from the preceding macro-scale plastic deformation. Accordingly, the fatigue failure should occur in the softest microstructural region; thus; the fatigue strength of the welded joint may be inferior to that of the original material.